2003
DOI: 10.1016/s0008-6363(03)00468-1
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular effects of erythropoietin

Abstract: Erythropoietin is a hypoxia-induced hormone that is essential for normal erythropoiesis. The production of recombinant human erythropoietin (rHuEpo) has revolutionized the treatment of anemia associated with chronic renal failure and chemotherapy, and has been used as prophylaxis to prevent anemia after surgery. The erythropoietin receptor is widely distributed in the cardiovascular system, including endothelial cells, smooth muscle cells and cardiomyocytes. Epo has potentially beneficial effects on the endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
197
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(209 citation statements)
references
References 116 publications
6
197
1
5
Order By: Relevance
“…Furthermore, erythropoietin can activate platelets, thereby potentially enhancing thrombosis risks when used in patients with preexisting cardiovascular disease. [28][29][30] Our study describes for the first time an association between mortality and high ESA dose in children and in a PD population. The link of high administered ESA doses with poor patient survival was independent of the Hb level achieved and more discriminative than the association of survival with the mean Hb level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, erythropoietin can activate platelets, thereby potentially enhancing thrombosis risks when used in patients with preexisting cardiovascular disease. [28][29][30] Our study describes for the first time an association between mortality and high ESA dose in children and in a PD population. The link of high administered ESA doses with poor patient survival was independent of the Hb level achieved and more discriminative than the association of survival with the mean Hb level.…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial effects of Epo may override potential Epo-related side effects such as elevated blood pressure and the incidence of thrombosis. 25 In addition to the use of cytokines to mobilize EPC from the bone marrow, several pharmacological substances have been shown to increase EPC numbers. 3-Hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, or statins, have been developed as lipid-lowering drugs, but besides lipid-lowering, statins are capable of reducing vascular inflammation, decreasing platelet aggregation and thrombus deposition, and increasing endothelium-derived nitric oxide (NO) production.…”
Section: Mobilization Of Epcs For Improvement Of Neovascularizationmentioning
confidence: 99%
“…Early tubulointerstitial occurs which disease decreases EPO production and moreover inflammatory cytokines reduce EPO responsiveness leading to anaemia [174]. It is also associated with the level of albuminuria [128] .Anaemia in turn, increases the progression toward CKD, oxidative stress, tissue ischemia, ventricular stress and mortality [175][176][177]. Of interest, a recent study demonstrated the contribution of anemia to the frequent diastolic dysfunction in DM, as well as its association with brain natriuretic peptide (BNP) and suggested using this factor to identify diabetic patients at increased risk of cardiac dysfunction [175].…”
Section: Rationale For Inclusion Of the Componentsmentioning
confidence: 99%